2011
DOI: 10.1007/s11027-011-9297-7
|View full text |Cite|
|
Sign up to set email alerts
|

Damage from the Great East Japan Earthquake and Tsunami - A quick report

Abstract: The Tohoku region, Northeast Japan, was hit by a gigantic earthquake which occurred in the Pacific close to Tohoku, and subsequently by a giant tsunami. These hazards have caused huge damage on the eastern coast Japan. The earthquake's magnitude was 9.0, the strongest ever recorded in Japan. The tsunami was also historical as its run-up height reached over 39 m. As of early May, 2011, over 24 thousand people were reported as dead or missing. Moreover, serious accidents at the Fukushima Nuclear Power Plants No.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
127
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 283 publications
(131 citation statements)
references
References 1 publication
3
127
0
1
Order By: Relevance
“…This catastrophic earthquake and tsunami resulted in the complete collapse of 118,480 houses and partial damage to 179,697 houses (NPA 2011). After the earthquake, there were 345 fires in 12 prefectures, including some cases where the tsunami triggered the fire (Mimura et al 2011). The damage to infrastructure was also very widespread, including damage to 3,559 areas along roads, 77 bridges, and 29 parts of the railway system (NPA 2011).…”
Section: Damage In Japan From the 2011 Tohoku Eventmentioning
confidence: 99%
See 4 more Smart Citations
“…This catastrophic earthquake and tsunami resulted in the complete collapse of 118,480 houses and partial damage to 179,697 houses (NPA 2011). After the earthquake, there were 345 fires in 12 prefectures, including some cases where the tsunami triggered the fire (Mimura et al 2011). The damage to infrastructure was also very widespread, including damage to 3,559 areas along roads, 77 bridges, and 29 parts of the railway system (NPA 2011).…”
Section: Damage In Japan From the 2011 Tohoku Eventmentioning
confidence: 99%
“…In some prefectures, it is difficult to determine if the cause of death was due to the earthquake or the tsunami; but according to a Jiji Press Report (2011), as of 19 April 2011, the analysis indicated that over 90% of the deaths were due to drowning in the Iwate, Miyagi and Fukushima Prefectures. The number of refugees exceeded 350,000 at one time (Mimura et al 2011). The earthquake and tsunami also caused the worst nuclear emergency since Chernobyl (RFI 2011).…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations